Viral keratitis after the second and third doses of inactivated COVID-19 vaccination: A case report - Huimin Shan; Ruoshuang Jia; Wenhui Liu; Xinyi Wu (Taylor & Francis Group, 2022)
Rare cases of viral keratitis after coronavirus disease 2019 (COVID-19) vaccination have been reported. Furthermore, to our knowledge, cases of viral keratitis after two rounds of COVID-19 vaccination have not yet been reported. We report the case of a 19-year-old man without a history of keratitis, who developed viral keratitis soon after receiving the second and third doses of inactivated COVID-19 vaccines. Each time after the patient received treatment with topical and systemic drugs, his ocular symptoms were gradually relieved, and corrected visual acuity in both eyes returned to normal. COVID-19 vaccination may be associated with rare cases of the development of keratitis in individuals without a medical history of keratitis. Physicians should be aware of the possible relationship between ocular symptoms and adverse reactions to the COVID-19 vaccination. Despite the potential risks of COVID-19 vaccination, the benefits of immunization against the virus far outweigh these risks.